KAJIAN PEMANFAATAN PRESIDENSI G20 INDONESIA DITINJAU DARI SEKTOR PERDAGANGAN BILATERAL INDONESIA DAN JEPANG - Ida Bagus Made Maha Dwi Putra; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Journal, 2022)
This study aims to describe the Utilization Analysis of Indonesia's G20 Presidency in terms of the Bilateral Trade Sector of Indonesia and Japan through an IJEPA (Indonesia-Japan Economic Partnership Agreement) agreement in the influence of Indonesia as the Presidency or host of the implementation of the G20. In it’s connection, Indonesia at the G20 forum is an advantage in various international economic systems in increasing Indonesia's economic growth.The research method used in this study is a Qualitative research method. The data collection technique in this study uses literature or literature techniques sourced from online media and print media. The results of this study explain that Indonesia's participation in the official G20 forum greatly affects Indonesia's opportunities in increasing both international and bilateral cooperation in the economic sector, especially trade, namely with the IJEPA (Indonesia-Japan Economic Partnership Agreement) agreement which benefits both countries. The many benefits obtained from Japan and Indonesia also prove that this bilateral relationship runs effectively and has many positive impacts both for the government and for Indonesian citizens themselves.